A public health concern: Chronic low back pain and the relationship between pain, quality of life, depression, anxiety, and sleep quality - Mammadov, Tariyel; Bölük Şenlikci, Hüma; Ayaş, Şehri (Journal of Surgery and Medicine, 2020)
Aim: Chronic low back pain (CLBP) is a common condition of the musculoskeletal system and a public health concern. CLBP patients suffer from conditions such as muscle weakness and numbness, resulting in diminished quality of life (QoL), poor functioning, psychological disorders and sleep disorders related to disabling pain. The aim of the current study was to reveal relationship between CLBP and patients’ health related QoL, anxiety, depression, and sleep disturbances.Methods: Seventy-three patients with CLBP and 73 healthy controls participated in this questionnaire-based cross-sectional study. The Short form McGill Pain Questionnaire, Roland-Morris disability, Short form-36 (SF-36), Beck Depression (BDI) and anxiety inventory (BAI) and the Pittsburgh Sleep Quality Index (PSQI) were used in the study group, and SF-36, BDI, BAI and PSQI were used in the control group. The relationships between QoL, depression, anxiety, and sleep disorders were examined in the two groups.Results: Two groups did not differ in terms of demographic characteristics (P>0.05). In the sub-scales of SF-36, except vitality and mental health, a significant difference was detected between the study and control groups (P<0.001). The depression, anxiety and PSQI scores did not differ between the two groups (P>0.05).Conclusion: CLBP affects QoL negatively. This should be considered when managing CLBP.